Shaken Authority : China's Communist Party and the 2008 Sichuan Earthquake - Sorace, Christian P. (Ithaca, NY : Cornell University Press, 2017)
In Shaken Authority, Christian P. Sorace examines the political mechanisms at work in the aftermath of the 2008 Sichuan earthquake and the broader ideological energies that drove them. Sorace takes Communist Party ideas and discourse as central to how that organization formulates policies, defines legitimacy, and exerts its power. Sorace argues that the Communist Party has never abandoned its conviction that discourse can shape the world and the people who inhabit it. Sorace also demonstrates how the Communist Party's planning apparatus continues to play a crucial role in engineering China's economy and market construction, especially in the countryside.Sorace takes a distinctive and original interpretive approach to understanding Chinese politics, and Shaken Authority demonstrates how Communist Party discourse and ideology influenced the official decisions and responses to the Sichuan earthquake. Sorace provides a clear view of the lived outcomes of Communist Party plans, rationalities, and discourses in the earthquake zone. The three case studies he presents each demonstrate a different type of reconstruction and model of development: urban-rural integration, tourism, and ecological civilization. Sorace's work emphasizes the need for a grounded literacy in the political concepts, discourses, and vocabularies of the Communist Party itself. To dismiss China's official discourse as "empty propaganda," Sorace argues, makes China and Chinese realities harder to understand, not easier.
Frontmatter -- Contents -- Acknowledgments -- Maps -- Introduction -- 1. The Communist Party's Miracle -- 2. Party Spirit Made Flesh -- 3. Blood Transfusion, Generation, and Anemia -- 4. The Utopia of Urban Planning: Dujiangyan Municipality -- 5. The Mirage of Development: Yingxiu Township -- 6. The Ideological Pursuit of Ecology: Qingchuan County -- Conclusion -- Notes -- Glossary of Terms and Phrases -- Bibliography -- Index
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 08. Jul 2019)
Keywords: Earthquake relief -- China -- Wenchuan Xian (Sichuan Sheng); Earthquake relief -- China -- Wenchuan Xian (Sichuan Sheng).; Emergency management -- China -- Wenchuan Xian (Sichuan Sheng); Emergency management -- China -- Wenchuan Xian (Sichuan Sheng).; Wenchuan Earthquake, China, 2008.; Asian Studies; 2 -- isacsh